Actinobacillus actinomycetemcomitans and Bacteroides gingivalis activate human peripheral monocytes to produce interleukin-1 and tumor necrosis factor - Lindemann, R A; Economou, J S (Journal of periodontology (1970), 1988)
The effects of gram-negative bacteria clearly associated with juvenile and adult periodontitis on monokine production were assessed using standard in vitro assay techniques. Actinobacillus actinomycetemcomitans and Bacteroides gingivalis were able to activate human peripheral blood monocytes to produce significant amounts of interleukin-1 (IL-1) and tumor necrosis factor (TNF). These monokines are known to induce osteoclastic bone resorption. An oral gram-positive organism, Staphylococcus epidermidis, was able to induce only modest amounts of IL-1 and TNF, slightly above unstimulated monocyte levels.